ChemInform Abstract: Developing Catalytic Asymmetric Acetalizations. Issue 41 (19th September 2013) - Coric, Ilija; Vellalath, Sreekumar; Mueller, Steffen; Cheng, Xu; List, Benjamin
Abstract Review: 58 refs.